Literature Review of Factors Affecting Occupational Safety Culture - Harahap, Aswin Syapii; Cahaya, Yohanes Ferry (Dinasti Publisher, 2025)
Work safety culture has become very important for companies to implement. With a good safety culture, the company will have a lower rate of workplace accidents, higher operational efficiency, and greater trust from employees and stakeholders. Building a strong safety culture is not easy; many challenges and obstacles occur in the field. This study aims to conduct a literature review of previous research on safety culture to identify the factors that influence the development of a good safety culture in companies. The research method used is qualitative research with content analysis techniques on 17 research papers with the keyword